PD

Tìm tập các giá trị của x thỏa mãn đẳng thức:

(x-3)\(^{x+1}\)- (x-3)\(^{11}\)=0

DD
12 tháng 8 2017 lúc 9:51

câu hỏi tương tự

Bình luận (0)
BA
12 tháng 8 2017 lúc 10:57

<=>\(\left(x-3\right)\left[\left(x-3\right)^x-\left(x-3\right)^{10}\right]=0\)

<=>\(\orbr{\begin{cases}x-3=0\\\left(x-3\right)^x-\left(x-3\right)^{10}=0\end{cases}}\)

<=>\(\orbr{\begin{cases}x=3\\\left(x-3\right)^x=\left(x-3\right)^{10}\end{cases}}\)

<=>\(\orbr{\begin{cases}x=3\\x=10\end{cases}}\)

Vậy x={3 ; 10}

Bình luận (0)